Attitude Construction toward Invasive Species through an Eco-Humanist Approach: A Case Study of the Lesser Kestrel and the Myna - Adiv Gal (Education Sciences, 2023)
The green school in northern Israel has embraced an eco-humanist approach with the aim of mitigating the animosity displayed by fifth-grade students towards invasive species. This antipathy arose due to the negative impact of these invasive species on a local species that the students were monitoring as a component of their environmental education curriculum. Therefore, the purpose of this study was to examine to what extent, if at all, there is a difference in the ethical attitude of the 188 fifth-grade students (10–11 years old) towards the conflict between the Lesser Kestrel (local species) and the Myna (invader species) and the solution to this conflict following the change to an eco-humanist teaching approach. The study, based on content analysis methodology of written self-reflection, and thematic analysis indicated that the fifth-graders’ knowledge was not adversely affected, but the solutions they proposed for resolving the conflict between the Myna and the Lesser Kestrel were more holistic, ethical, and moral after adopting the eco-humanist approach. Eco-humanism encourages an ethical attitude and environmental responsibility toward nature’s fate, including invasive species.